Analisis minat mahasiswa terhadap penggunaan e-wallet sebagai alat transaksi - Kurniawati, Lina (Maliki Interdisciplinary Journal, 2023)
The rapid development of technology makes it easier for startup companies in the financial sector to make the latest innovations, such as making applications from digital wallets. A digital wallet (e-wallet) is a tool that is used as a means of non-cash payment transactions made to facilitate the effectiveness of payments. Today’s young generation is very interested in something that is effective and efficient. Including interest in using digital wallets which will easily help them transact in non-cash payments. This study aims to analyze student interest in using e-wallets. This research was conducted using a questionnaire instrument made with a closed questions system. By using this system, respondents can quickly and easily answer the questionnaire so that the questionnaire data can be analyzed statistically quickly. The results of this study indicate that overall the number of respondents is interested in using the e-wallet application and even they have used more than one e-wallet application. Based on the results of these data, the ShopeePay application is the most user application of the total number of respondents using the e-wallet application.